Non-pegylated and Pegylated Interferon Alpha-2a in Cutaneous T-cell Lymphoma and the Risk of Severe Ocular Side-effects - Jana D. Albrecht; Nadia Ninosu; Denise Barry; Thomas Albrecht; Marthe-Lisa Schaarschmidt; Sergij Goerdt; Jan P. Nicolay (Medical Journals Sweden, 2022)
Abstract is missing (Short communication)